Social development versus economic growth: current contradictions and perspectives of convergence. Issue 1 (18th May 2020) - Bogoviz, Aleksei V.; Lobova, Svetlana V.; Alekseev, Alexander N.
Abstract : Purpose: The purpose of the research is to determine the current contradictions and perspectives of convergence of social development and economic growth for the purpose of formation of the scientific and methodological basis of targeted and efficient state regulation of these processes, which would allow for their harmonization and systemic acceleration. Design/methodology/approach: The authors use correlation analysis for calculating the correlation of the rate of economic growth (according to the forecast of the IMF) and the indicators of qualify of life, calculated by Numbeo, and the index of economy digitization, calculated by the IMD. The research is performed based on the 2020 data. On the basis of the established dependencies, the authors use the method of hierarchy analytics of T.L. Saaty for determining the contribution of social development into economic growth. Findings: The authors substantiate the existence of close interconnection between social development and economic growth and determine substantial differences in this interconnection in developed countries (correlation – 52%), where only purchasing power of population and society's digitization contribute into acceleration of economic growth, and in developing countries (correlation – 48%), where quality of life, environment protection, living standards and society's development level contribute to acceleration of economic growth. Originality/value: It is proved that in the course of the increase of the level of social development, it contradicts economic growth – due to which the possibilities of state regulation of the interconnection of these processes are limited. The authors develop a conceptual model of convergence of these processes through the prism of phases of the economic cycle. The compiled model reflects the authors' recommendations at each phase of the economic cycle, due to which state regulation of socioeconomic development will become targeted and efficient.